Student Creativity in Using Audio-Visual-Based Learning Media - Kasman, Kasman; Nur, Kholidah; Wulandari, Martina Ayu (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study examined student creativity in using audio-visual media in material presentation in class. This research used a descriptive qualitative approach. It is a case study research conducted on first-semester students of the PIAUD study program at STAIN Mandailing Natal. In this study, the research data was students' usage of learning media obtained from students and lecturers. Data collection techniques involved observation, interviews, and documentation, while data analysis consisted of data reduction, data presentation, and conclusion drawing. The results showed that the students' use of learning media increased their creativity, with the lecturers only providing themes, input, and directions. The students designed and compiled learning videos for the lecture processed their creativity, generated new ideas, and created innovation to make the learning more interesting and to add insight into science and technology. In addition, students' use of learning media increased their creativity and generated ideas on what materials to use for their videos; as a result, the media could be put to good use, and the lectures could run more effectively and efficiently.